2002
DOI: 10.1034/j.1600-0781.2002.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Age dependence of ultraviolet light‐induced erythema following narrow‐band UVB exposure

Abstract: Narrow-band UVB therapy may, in case of over dosage, produce more intense erythema in the late phase of UVB erythema in old people than in younger individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 19 publications
1
14
2
2
Order By: Relevance
“…However, a significant degree of apoptosis was already observed at the doses of about 800–1000 mJ/cm 2 depending on studied cell types and conditions of irradiation [20,22]. Importantly, an apoptotic dose of NB-UVB is very similar to the minimal erythema dose (MED) of NB-UVB observed by Gloor and Scherotzke [32] in Caucasian subjects, indicating that indeed UV-induced erythema might be an inflammatory response to the appearance of “sunburn cells” ( i.e ., apoptotic cells) in native human epidermis. Broad-band UVB and NB-UVB at equivalent MED doses were equally potent in inducing p53 and p16 expression as well as apoptosis in healthy volunteers [33].…”
Section: Narrow Band Uvb (311 Nm) and Apoptosis Of Keratinocytesmentioning
confidence: 68%
“…However, a significant degree of apoptosis was already observed at the doses of about 800–1000 mJ/cm 2 depending on studied cell types and conditions of irradiation [20,22]. Importantly, an apoptotic dose of NB-UVB is very similar to the minimal erythema dose (MED) of NB-UVB observed by Gloor and Scherotzke [32] in Caucasian subjects, indicating that indeed UV-induced erythema might be an inflammatory response to the appearance of “sunburn cells” ( i.e ., apoptotic cells) in native human epidermis. Broad-band UVB and NB-UVB at equivalent MED doses were equally potent in inducing p53 and p16 expression as well as apoptosis in healthy volunteers [33].…”
Section: Narrow Band Uvb (311 Nm) and Apoptosis Of Keratinocytesmentioning
confidence: 68%
“…The subjects' ages in the present study range from 15 to 50 years. It has been shown that UVB radiation causes more intensive erythema in older subjects [41] and induces a more dramatic increase in TEWL in younger mice (27 weeks old) than in older ones, which shows a minimum increase (90 weeks old) [42] . Although suberythemal UVB radiation accelerates barrier recovery in the animal model [37] , in the present study no dramatic difference in barrier recovery was observed between control and lower doses of sun exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum erythema occurs 8-24 h after irradiation (125,126). As patients over 70 years show a prolonged nUVB-induced erythema, a more cautious approach to dose increases is recommended in the elderly (127).…”
Section: Early Side Effectsmentioning
confidence: 99%